The flight of a kite. Critical extension experience in Paraná, Argentina (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
Within the framework of a safeguarding project of elements of intangible cultural heritage in Paraná (Province of Entre Ríos, Argentina), a series of conversations and workshops among the references from the Provincial Museum of the Eva Perón Home School in this city and the team of extension and research, as part of a critical extension experience. From this interaction, in August 2022 the 'chocobarrileteada' was organized in the museum park. This was an opportunity to develop participant observation and reflect on community practices that recover the collectives games with the technique of making a popular toy: the kite.
Keywords: games; community; intangible cultural heritage; critical extension